Comparison between N-butyl cyanoacrylate tissue adhesive and Ethilon nylon sutures in extraoral maxillofacial incisions: A randomized prospective study - Sudipto Sahu; Sobhan Mishra; Sthitaprajna Lenka; Rajarshi Banerjee; Sandeep Pachisia; Sucharu Ghosh (Elsevier, 2019)
Objectives: Wound closure is a part of any surgical procedure. Wound care and healing process are concepts, which are usually reliant upon sutures. The suture and non-suture repair of the tissues has been a major concern to surgeons for over four thousand years. The objective of this study is to compare the rates of infection, wound dehiscence, necrosis and time required by N-butyl cyanoacrylate tissue adhesive and nylon sutures in extraoral maxillofacial wound closer. Materials and methods: 24 patients requiring external wound closing were included in this study. Patients were divided in two groups, in one group wound closer was done by N-butyl cyanoacrylate tissue adhesive and by conventional nylon suture in the other group. The software STATA® of StataCorp was used in statistical analysis if this study. Results: Wound infection, dehiscence, necrosis of tissue edges, time taken for closure was much less in case of tissue adhesive than conventional sutures. Conclusion: Advantages of tissue adhesives over conventional wound closure techniques include easy to use, excellent bacteriostatic property, decreased repair time, elimination of recall visits and comparable short and long-term cosmetic outcome. Though tissue adhesives have many advantages over conventional wound closure techniques, they can be used as an alternative to sutures only in superficial small and tension free skin incisions or lacerations.